(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
During 2007-2013 years 103 species of agaricoid macromycetes from 51 genera, 20 families, 3 orders (Agaricales, Boletales і Russulales) of class Agaricomycetes аre revealed. The article provides the list of fungi species with distribution to ecotops of region. Taxonomic analysis, distribution to ecological trophical groups, determination properties and taxonomic indexes of mycobiota are reported. The similarity of species composition from different ecotops are presented. Novelty of macromycetes species for the Nоrthen- Western part оf the Black Sea region and steppe region of Ukraine are shown.